Systemic consequences of abnormal cholesterol handling: Interdependent pathways of inflammation and dyslipidemia - O’Hagan, Ross; Berg, Alex R.; Hong, Christin G.; Parel, Philip M.; Mehta, Nehal N.; Teague, Heather L. (Frontiers in Immunology, 2022)
Metabolic conditions such as obesity and associated comorbidities are increasing in prevalence worldwide. In chronically inflamed pathologies, metabolic conditions are linked with early onset cardiovascular disease, which remains the leading cause of death despite decades of research. In recent years, studies focused on the interdependent pathways connecting metabolism and the immune response have highlighted that dysregulated cholesterol trafficking instigates an overactive, systemic inflammatory response, thereby perpetuating early development of cardiovascular disease. In this review, we will discuss the overlapping pathways connecting cholesterol trafficking with innate immunity and present evidence that cholesterol accumulation in the bone marrow may drive systemic inflammation in chronically inflamed pathologies. Lastly, we will review the current therapeutic strategies that target both inflammation and cholesterol transport, and how biologic therapy restores lipoprotein function and reduces the immune response.